1966
DOI: 10.1677/joe.0.0350363
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the Androgen Antagonist Cyproterone Acetate on the Testicular Structure, Spermatogenesis and Accessory Sexual Glands of Testosterone-Treated Adult Hypophysectomized Rats

Abstract: SUMMARY The antagonistic action of 1,2α-methylene-6-chloro-Δ4,6-pregnadiene-17α-ol-3,20-dione-17α-acetate (cyproterone acetate) to testosterone propionate (TP) on the testes and accessory glands was investigated in hypophysectomized adult male rats. Treatment of the animals began on the day of hypophysectomy and was continued for 21 days. Daily subcutaneous injections of 0·3 or 1·5 mg. TP/100 g. body weight almost completely inhibited testicular atrophy and involution of the germinal epithelium… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
20
0
1

Year Published

1970
1970
2011
2011

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 108 publications
(21 citation statements)
references
References 0 publications
0
20
0
1
Order By: Relevance
“…It is reported that the IL-8 gene activation is regulated by NF-kB, C/EBP and AP-1, each of them alone or in synergy, depending on cell type. 23) In MH7A cells the NF-kB binding site in the promoter region of the IL-8 gene appeared to be critical for the IL-1a or TNFa-induced transactivation of the gene. This was confirmed by the observation that NF-kB, ei- ther IL-8 gene-or Ig-kB-derived, was markedly activated by IL-1a or TNFa, while C/EBP and AP-1 were not at all or only slightly activated.…”
Section: Discussionmentioning
confidence: 92%
“…It is reported that the IL-8 gene activation is regulated by NF-kB, C/EBP and AP-1, each of them alone or in synergy, depending on cell type. 23) In MH7A cells the NF-kB binding site in the promoter region of the IL-8 gene appeared to be critical for the IL-1a or TNFa-induced transactivation of the gene. This was confirmed by the observation that NF-kB, ei- ther IL-8 gene-or Ig-kB-derived, was markedly activated by IL-1a or TNFa, while C/EBP and AP-1 were not at all or only slightly activated.…”
Section: Discussionmentioning
confidence: 92%
“…Miullerian duct suppression, while there were varying degrees of incomplete Wolffian development, phallic growth, and labioscrotal and urethral development. There is ample evidence to support the theory of Jost (22)(23)(24) that the testis plays an inducer role in the Miillerian suppression and that this inducer is not testosterone (25). Further, the development of the Wolifian system apparently requires both inducer substance and androgen while external genitalia are largely dependent on androgen.…”
Section: Discussionmentioning
confidence: 91%
“…To determine whether the inhibitory effect of DHT was mediated by AR, MH7A cells were treated with TNFa with or without DHT in the presence or absence of androgen receptor antago- nist, hydroxyflutamide (OHF). 21) As shown in Fig. 2B, OHF significantly reversed the inhibitory effect of DHT.…”
Section: Resultsmentioning
confidence: 59%